As significações dos professores de Educação Física Escolar sobre a função de seu componente curricular - Silva, Fabricio Vilela (2024)
This study investigates the meanings attributed by teachers to the role of school Physical Education, based on Socio-Historical Psychology and using HistoricalDialectical Materialism as a method. It aims to understand the meanings elementary teachers attribute to Physical Education in the school context and analyze the mediations shaping these meanings in relation to pedagogical practices. The research subjects were two male teachers and one female teacher, with additional insights from the school principal and coordinator. This research is justified by the need to critically reflect on the role of Physical Education as a curricular component and its potential to contribute to students’ holistic education. The methodology included interviews at a Municipal School in São Bernardo do Campo, with responses recorded, transcribed, and grouped into three Meaningful Units. The first unit reveals an instrumental view of Physical Education; the second emphasizes its role in developing critical, healthy individuals; and the third discusses the need to move beyond a recreational perspective. Results show that Physical Education is affected by multiple mediations and often occupies a secondary role compared to other curricular components. The interaction among the Meaningful Units reveals the complexity of school Physical Education, demonstrating that while often treated as supplementary, there is a movement to re-signify it as essential for holistic development. Teachers face the challenge of reconciling historical mediations with contemporary expectations, striving to transcend a view focused solely on leisure or motor skills. However, for this transformation to solidify, Physical Education requires public policies that value it as a curricular component and ensure adequate working conditions. This research highlights the importance of ongoing critical education that integrates body, movement, and a comprehensive view of education, reinforcing Physical Education as a promoter of reflective and civic education